Análise não-linear de sistemas mistos para a obtenção de larguras efetivas e carregamentos de vigas no estado limite último - Sidnea Eliane Campos Ribeiro (1997)
The effective slab widyh incorporated to composite floor beams is usually based on simplified rules taken from the relevant codes. The tributary areas for the beams are often based on some plastic hinge mechanism of the slab, neglecting the vertical deflections of the beams. These procedures are used for both ultimate and serviceability limit states, a series of non-linear FEM analysis are carried out. The selected ranges of the main parameters are based on practical situations. Some design recommendations are presented together with the final conclusions.